2018
DOI: 10.1002/pola.29175
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable poly(ether amide)s from lignin‐derived precursors

Abstract: In recent years, there have been concerted efforts to replace petrochemical products with those from renewable sources due to the unsustainability of petroleum feedstock, and the continued volatility in the price. This work describes the synthesis and thermal properties of two new lignin‐derived poly(ether‐amide)s as alternative thermoplastics to petroleum‐based commodities. Poly‐4‐(2‐aminoethoxy)benzoate (PEAB) and poly‐4‐(2‐aminoethoxy)‐3‐methoxybenzoate (PEAV) are synthesized by a melt polycondensation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Lignin valorization has the potential to replace completely fossil‐based aromatic polymers . By synthesizing two poly(ether amide)s from lignin‐derived precursors, Saenz and Scott showed that lignin‐based polymers are achievable . Other recent studies have shown that lignin could also be used to produce UV‐curable coatings, nanoparticles, elastomers, anticorrosion coating for metal surfaces, and carbon fibers .…”
Section: Introductionmentioning
confidence: 99%
“…Lignin valorization has the potential to replace completely fossil‐based aromatic polymers . By synthesizing two poly(ether amide)s from lignin‐derived precursors, Saenz and Scott showed that lignin‐based polymers are achievable . Other recent studies have shown that lignin could also be used to produce UV‐curable coatings, nanoparticles, elastomers, anticorrosion coating for metal surfaces, and carbon fibers .…”
Section: Introductionmentioning
confidence: 99%